A pediatric digital storytelling system for third year medical students: The Virtual Pediatric Patients - D'Alessandro Michael P; Lewis Tamra E; D'Alessandro Donna M (BMC Medical Education, 2004)
Abstract Background Computer-based patient simulations (CBPS) are common, effective, instructional methods for medical students, but have limitations. The goal of this project was to describe the development of a CBPS designed to overcome some of these limitations and to perform an online evaluation. Methods In 1996, patients and families experiencing a common pediatric problem were interviewed, photographed and a chart review completed. A digital storytelling template was developed: 1. patient's story, evaluation and clinical course, 2. problem-based approach to the evaluation, and 3. discussion of disease process. The media was digitized and placed onto the Internet. The digital stories and a 10-question online survey were pilot tested. Online survey responses were collected from 1999–2003. Overall use of the digital stories was measured by computer server logs and by the number of hyperlinks to the CBPS. Results Eight stories were created using this system. Over 4.5 years, 814,148 digital story pages were read by 362,351 users. Hyperlink citations from other websites to the CBPS were 108. Online survey respondents (N = 393) described the overall quality as excellent or very good (88.4%). The stores were clearly written (92%) at an appropriate level (91.4%). Respondents felt they could begin to evaluate a similar case presentation (95.4%), and would remember the case in the future (91%). Conclusions A new type of CBPS, the digital storytelling system, has been developed and evaluated which and appears to be successful in overcoming some of the limitations of earlier CBPS by featuring patient's stories in their own words, by focusing on problems rather than diseases, and by having stories that are quick for students to work through.